A General and Extremely Simple Remote Approach toward Graphene Bulks with In Situ Multifunctionalization. Issue 17 (2nd March 2016) - Cheng, Huhu; Ye, Minghui; Zhao, Fei; Hu, Chuangang; Zhao, Yang; Liang, Yuan; Chen, Nan; Chen, Shilv; Jiang, Lan; Qu, Liangti
Abstract : Functional graphene bulks are developed by a general and simple approach for largescale preparation. This method shows promise for energy‐related applications.